Volume 2: Processes; Materials 2019
DOI: 10.1115/msec2019-2977
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of the Hot Forming Process of Composite Materials

Abstract: We present a fully coupled thermomechanical simulation of the hot forming process of composite materials. The raw material is a mixture of resin powders, strengthening particles and reinforcing fibers. Complex material responses in the process, such as phase change (melting and polymerization) and reorientation of the fibers, determine the microstructure and the performance of the final product. A phase-aware incremental mesh-free Lagrangian method is presented to overcome the challenges, which combines the Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Gleeble 1500 thermal simulation testing machine is used as shown in Figure 5(a). e test method as shown in Figure 5(b) is as follows: (1) samples are heated to 950°C at 10°C/s; (2) samples are put into the heating furnace for 120 s to make them fully austenite; (3) the heating sample is cooled down to 850°C at 30°C/s and kept heating preservation for 10s; (4) tensile experiment is conducted for each sample at a strain rate of 0.3 s −1 to a true strain of 0.2 with Gleeble 1500; and (5) these samples are cooled down at a cooling rate of 20°C/s, 30°C/s, 40°C/s, 50°C/s, 70°C/s, and 100°C/s to room temperature, respectively. Effects of cooling rate could be concluded by observing the microstructure of these samples.…”
Section: Cooling Rate Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gleeble 1500 thermal simulation testing machine is used as shown in Figure 5(a). e test method as shown in Figure 5(b) is as follows: (1) samples are heated to 950°C at 10°C/s; (2) samples are put into the heating furnace for 120 s to make them fully austenite; (3) the heating sample is cooled down to 850°C at 30°C/s and kept heating preservation for 10s; (4) tensile experiment is conducted for each sample at a strain rate of 0.3 s −1 to a true strain of 0.2 with Gleeble 1500; and (5) these samples are cooled down at a cooling rate of 20°C/s, 30°C/s, 40°C/s, 50°C/s, 70°C/s, and 100°C/s to room temperature, respectively. Effects of cooling rate could be concluded by observing the microstructure of these samples.…”
Section: Cooling Rate Testsmentioning
confidence: 99%
“…If the usage of UHSS in auto body reaches up to 80%, the total weight of auto body decreases by 20% on the premise of the same cost [1]. us, the UHSS and its hot forming technology hold wide prospects in the automobile industry, especially for some critical crash components such as A-pillars, B-pillars, and side rails [2][3][4]. During the hot stamping process of UHSS, the blank is initially austenitization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that conducting material research solely through experimental methods not only incurs high costs, but also in many cases, leads to a lack of information on microstructure evolution mechanisms, and it cannot explain conflicting data, resulting in the inability to identify true patterns [14]. The advantages of numerical simulation techniques have been gradually highlighted with the progress of science and technology, and the use of computer technology to study modern science has become a proven scientific aid [15].…”
Section: Introductionmentioning
confidence: 99%